School Digital Reputation Management Through Social Media: an Integrative Review and Conceptual Framework - Muhammad Syaikhul Basyir; Nur Saidah; Syaiful Kiram; Hanif Firdaus; Erik Junaedi (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2026)
Digital platforms have expanded the arenas in which schools are evaluated, yet the literature often treats social media, branding, trust, and reputation as separate issues. This study synthesizes recent evidence and develops a school-focused conceptual framework for digital reputation management. A structured integrative literature review was conducted using Google Scholar, ScienceDirect, Taylor & Francis Online, SpringerLink, Emerald Insight, Garuda/Sinta, and official journal portals. Searches undertaken on 20–25 July 2026 and updated on 1 August 2026 identified 42 records. After four duplicates were removed, 38 records were screened, 28 full texts were assessed, and 20 publications from 2022–2026 met the eligibility and quality threshold. The corpus was appraised for topical relevance, methodological transparency, source credibility, and transferability to school settings, then analyzed through content coding and thematic synthesis. Six themes were identified: social media governance; digital branding and content credibility; stakeholder engagement; public trust; digital reputation risk; and educational competitiveness as a potential outcome. The synthesis distinguishes organizational branding efforts from reputation as an external, cumulative stakeholder evaluation. It proposes that governance enables credible content, engagement supports trust formation, and trust contributes to reputation, while risk management operates across the process. Any competitiveness benefit remains contingent on congruence between digital claims and actual educational service quality. The framework offers testable propositions and measurable managerial indicators for future school-based research.